PERAN JAPAN INTERNATIONAL COOPERATION AGENCY DALAM REVEGETASI LAHAN KRITIS PADA KALDERA GUNUNG BATUR, BALI DALAM KURUN WAKTU 2012-2014 - Deviyanti, Ni Luh Md.; Priadarsini, Ni Wayan Rainy; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Japan International Cooperation Agency (JICA) in particular has taken an important role in regards with supports for conservancy initiated by developing countries. The current research discusses JICA’s role in the revegetation of critically barren land of Balinese Mt Batur’s caldera during the period of 2012-2014. Revegetation is one of responsive attempts to rebuild barren ground with relevant procedures in a way the disturbed land returns to its naturally economic and social function for the society. Qualitative research method was used in the present study with secondary data collected from books and the web that provides description of conservancy roles of development agency. The findings shows that throughout its revegetation projects JICA has successfully repaired the eroded land. The rewilding projects have also been aiming at sustainable development as planted trees absorb water and therefore provides sustainable natural resources for the society. Keywords: Development Agency , Disturbed Lands, Japan International Cooperation Agency, Revegetasi , Sustainable Development.